Aeromycological study of monument in relation to environmental factors - Sharma, K; Nafis, Arshi (Current Botany, 2011)
Present investigation focuses on mycobial survey of ancient monument of Chhattisgarh and study carried out March 2010 to February 2011. During the present investigation period it was observed that fungal population was varying from season to season and month to month. Environmental factor play an important role for the distribution of the fungal spores. The Fungal population is not homogenous throughout the year and shows seasonal variation. It was observed that maximum fungal population was observed in winter season, due to favourable temperature and relative humidity, moderate in rainy season and minimum number of fungal population was recorded in summer season, possibly due to unfavourable temperature and relative humidity for mycoflora.Â